(untitled) - Marchewka, Jack T. (Hoboken, NJ, 2015)
The 5th Edition of Jack Marchewka's Information Technology Project Management focuses on how to create measurable organizational value (MOV) through IT projects. The author uses the concept of MOV, combined with his own research, to create a solid foundation for making decisions throughout the project's lifecycle.
Keywords: Công nghệ thông tin,Project management,Information technology,Quản lý dự án; Quản lý,Computer programs,Management,Chương trình máy tính